Cross-cultural validity of a dietary questionnaire for studies of dental caries risk in Japanese - C. Shinga-Ishihara; Yukie Nakai; Peter Milgrom; Kaori Murakami; Michiyo Matsumoto‐Nakano (2014)
Diet is a major modifiable contributing factor in the etiology of dental caries. The purpose of this paper is to examine the reliability and cross-cultural validity of the Japanese version of the Food Frequency Questionnaire to assess dietary intake in relation to dental caries risk in Japanese.The 38-item Food Frequency Questionnaire, in which Japanese food items were added to increase content validity, was translated into Japanese, and administered to two samples. The first sample comprised 355 pregnant women with mean age of 29.2 ± 4.2 years for the internal consistency and criterion validity analyses. Factor analysis (principal components with Varimax rotation) was used to determine dimensionality. The dietary cariogenicity score was calculated from the Food Frequency Questionnaire and used for the analyses. Salivary mutans streptococci level was used as a semi-quantitative assessment of dental caries risk and measured by Dentocult SM. Dentocult SM scores were compared with the dietary cariogenicity score computed from the Food Frequency Questionnaire to examine criterion validity, and assessed by Spearman's correlation coefficient (rs) and Kruskal-Wallis test. Test-retest reliability of the Food Frequency Questionnaire was assessed with a second sample of 25 adults with mean age of 34.0 ± 3.0 years by using the intraclass correlation coefficient analysis.The Japanese language version of the Food Frequency Questionnaire showed high test-retest reliability (ICC = 0.70) and good criterion validity assessed by relationship with salivary mutans streptococci levels (rs = 0.22; p < 0.001). Factor analysis revealed four subscales that construct the questionnaire (solid sugars, solid and starchy sugars, liquid and semisolid sugars, sticky and slowly dissolving sugars). Internal consistency were low to acceptable (Cronbach's alpha = 0.67 for the total scale, 0.46-0.61 for each subscale). Mean dietary cariogenicity scores were 50.8 ± 19.5 in the first sample, 47.4 ± 14.1, and 40.6 ± 11.3 for the first and second administrations in the second sample. The distribution of Dentocult SM score was 6.8% (score = 0), 34.4% (score = 1), 39.4% (score = 2), and 19.4% (score = 3). Participants with higher scores were more likely to have higher dietary cariogenicity scores (p < 0.001; Kruskal-Wallis test).These results provide the preliminary evidence for the reliability and validity of the Japanese language Food Frequency Questionnaire.